Surface charge changes in spike RBD mutations of SARS-CoV-2 and its variant strains alter the virus evasiveness via HSPGs: A review and mechanistic hypothesis - Zhang, Zhongyun; Zhang, Juan; Wang, Jiqiu (Frontiers in Public Health, 2022)
With the COVID-19 pandemic continuing, more contagious SARS-CoV-2 variants, including Omicron, have been emerging. The mutations, especially those that occurred on the spike (S) protein receptor-binding domain (RBD), are of significant concern due to their potential capacity to increase viral infectivity, virulence, and breakthrough antibodies' protection. However, the molecular mechanism involved in the pathophysiological change of SARS-CoV-2 mutations remains poorly understood. Here, we summarized 21 RBD mutations and their human angiotensin-converting enzyme 2 (hACE2) and/or neutralizing antibodies' binding characteristics. We found that most RBD mutations, which could increase surface positive charge or polarity, enhanced their hACE2 binding affinity and immune evasion. Based on the dependence of electrostatic interaction of the epitope residue of virus and docking protein (like virus receptors or antibodies) for its invasion, we postulated that the charge and/or polarity changes of novel mutations on the RBD domain of S protein could affect its affinity for the hACE2 and antibodies. Thus, we modeled mutant S trimers and RBD-hACE2 complexes and calculated their electrotactic distribution to study surface charge changes. Meanwhile, we emphasized that heparan sulfate proteoglycans (HSPGs) might play an important role in the hACE2-mediated entry of SARS-CoV-2 into cells. Those hypotheses provide some hints on how SARS-CoV-2 mutations enhance viral fitness and immune evasion, which may indicate potential ways for drug design, next-generation vaccine development, and antibody therapies.